Conducting polymers from aminobenzoic acids and aminobenzenesulphonic acids: influence of pH on electrochemical behaviour - Brett, Christopher M. A. (2002)
The influence of pH on the electrochemical behaviour of conducting polymer films electrosynthesised from aminobenzoic acids and aminobenzenesulphonic acids was investigated by voltammetric and electrochemical impedance studies in sulphuric acid solution, acetate buffer and neutral phosphate buffer. The change in electrochemical behaviour with increasing pH is significantly less for poly(aminobenzenesulphonic acid)s and poly(aminobenzoic acid)s than for polyaniline. Polymer films made by electrosynthesis of mixtures of these monomers with aniline have also been analysed by the same techniques. Experimental results obtained over this pH range are interpreted in the light of previous studies carried out on these polymers in strong acid solution.